Income tax revenues of local government units in Poland during the COVID–19 pandemic - Elżbieta Życzkowska; Jarosław Dziuba (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
IT and CIT tax revenues are an important source of financing for local government units (LGUs) in Poland influencing their ability to carry out public tasks. In the context of the COVID-19 pandemic, which significantly affected the economy, it has become particularly important to study changes in the level of these revenues and their consequences for the financial stability of LGUs. The purpose of this paper is to analyze PIT and CIT tax revenues as the crucial own-source revenues of local government units, with a particular focus on the pandemic period. The study aims at determining the extent to which the pandemic has affected these revenues. The study applies comparative and statistical analysis methods using data from the period 2019-2023. The analysis was based on the data provided by the Ministry of Finance. The dynamics of PIT and CIT revenues was compared before, during and after the pandemic period, taking into account the differences between various types of LGUs (municipalities, counties, voivodships).